The Impact of Trust in Fintech P2P Lending Users on Continuance Intention Through Perceived Benefits, Perceived Ease of Use, and Perceived Risk - Bakhri, Fajrur Rizal; Fauzia, Ika Yunia (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of perceived benefits, perceived ease of use and perceived risk on sustainable intentions through trust in fintech p2p lending users. The research method used is quantitative research used in this study including causal research. The sample consists of a research sample of at least 150 respondents of MSME business actors who are BPR customers in East Java Province. The results showed that perceived benefits had a significant positive effect on sustainability intentions, perceived ease of use had a significant positive effect on sustainability intentions, perceived risk had a significant negative effect on sustainability intentions, perceived benefits had a significant positive effect on trust, perceived ease of use had a significant positive effect on trust, perceived risk had a significant negative effect on trust, trust had a significant positive effect on sustainability intentions, perceived benefits had a significant positive effect on sustainability intentions, perceived ease of use had a significant positive effect on sustainability intentions through trust, lending in the trade sector, perceived risk had a significant negative effect on sustainability intentions through trust.